"Good Fences Make Good Neighbors": How does the Human Gut Microchip Unravel Mechanism of Intestinal Inflammation?. (3rd May 2020) - Shin, Woojung; Hackley, Landon A.; Kim, Hyun Jung
ABSTRACT: A microengineered human gut-on-a-chip has demonstrated intestinal physiology, three-dimensional (3D) epithelial morphogenesis, and longitudinal host-microbiome interactions in vitro . The modular accessibility and modularity of the microphysiological gut-on-a-chip can lead to the identification of the seminal trigger in intestinal inflammation. By coupling microbial and immune cells in a spatiotemporal manner, we discovered that the maintenance of healthy epithelial barrier function is necessary and sufficient to demonstrate the homeostatic tolerance of the gut. Here, we highlight the breakthrough of our new disease model and discuss the future impact of investigating the etiology and therapeutic targets in the multifactorial inflammatory bowel disease.